Olanzapine-Induced Mania in Bipolar Spectrum Disorder:A Case Report - Mehrdad Eftekhar; Amir Shabani (Iranian Journal of Psychiatry, 2006)
Objective: To report the case of a 46-year old male with major depressive disorder, who represented manic symptoms, when olanzapine was added to his treatment. Method: A 46-year old female, with a diagnosis of treatment resistant depression was referred to the authors. He had past history of depression for more than 20 years. The symptoms were present nearly every day since 1981, without any distinct period of remission, nor any noticeable fluctuation. His irritability had been disruptive to his family all these years. His doctor had prescribed maprotiline 25 mg/day, and lorazepam, 2mg/day, in addition to fluoxetine for the last 5 months. He is also a father of two children with methylphenidateresistant and sodium valproate-responsive attention-deficit hyperactivity disorder. Considering the antidepressant effects of olanzapine and its positive effects on irritability, the authors added olanzapine, to the patient’s previous medications. Results: After one week, he showed new problems such as talkativeness and beginning to smoke for the first time in his life, elevated mood, grandiosity about his intelligence and abilities, talkativeness, and shopping sprees. The score on the mania rating scale was 14. Fluoxetine was discontinued and sodium valproate, were prescribed. It took around 2 months to completely control the manic symptoms. Conclusions: In the patients with depression who show bipolar spectrum disorder features, adding mood stabilizers may be preferred to the drugs as olanzapine which could induce mania.